2021
DOI: 10.1186/s13073-021-00870-6
|View full text |Cite
|
Sign up to set email alerts
|

Rare deleterious mutations of HNRNP genes result in shared neurodevelopmental disorders

Abstract: Background With the increasing number of genomic sequencing studies, hundreds of genes have been implicated in neurodevelopmental disorders (NDDs). The rate of gene discovery far outpaces our understanding of genotype–phenotype correlations, with clinical characterization remaining a bottleneck for understanding NDDs. Most disease-associated Mendelian genes are members of gene families, and we hypothesize that those with related molecular function share clinical presentations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 130 publications
2
49
0
1
Order By: Relevance
“…Unsurprisingly, the majority of genes included in this review have multiple known, experimentally determined interactions (and these mainly include the DE-EE genes encoding for ion channels and receptors), while a second group of tightly connected genes involves transcription factors and chromatin modulators. Not unexpectedly, the two members of the heterogeneous nuclear ribonucleoproteins family HNRNPU and HNRNP2 appear functionally related to each other [97] but not with the main network, and additional genes with single RSS case descriptions lack evidence of functional connection or co-expression with the main network (Figure 3). Major alterations affecting several neurological processes, such as the regulation of synaptic transmission, inflammatory and stress-related processes, DNA binding and mRNA stability were confirmed in RTT with a transcriptomic approach [98].…”
Section: Clinical Remarksmentioning
confidence: 99%
“…Unsurprisingly, the majority of genes included in this review have multiple known, experimentally determined interactions (and these mainly include the DE-EE genes encoding for ion channels and receptors), while a second group of tightly connected genes involves transcription factors and chromatin modulators. Not unexpectedly, the two members of the heterogeneous nuclear ribonucleoproteins family HNRNPU and HNRNP2 appear functionally related to each other [97] but not with the main network, and additional genes with single RSS case descriptions lack evidence of functional connection or co-expression with the main network (Figure 3). Major alterations affecting several neurological processes, such as the regulation of synaptic transmission, inflammatory and stress-related processes, DNA binding and mRNA stability were confirmed in RTT with a transcriptomic approach [98].…”
Section: Clinical Remarksmentioning
confidence: 99%
“…To identify differentially expressed genes [DRGs as well as URGs (upregulated genes)], a paired differential gene expression (DGE) analysis (using patients/controls as covariate) was conducted by using DESeq2 package (Love et al, 2014) Bain-type ID (Bain et al, 2016(Bain et al, , 2021. Both NDDs result from monoallelic pathogenic variants preferentially affecting the nuclear localization domain, indispensable to nuclear transport of the hnRNPH1/H2proteins, though HNRNPH1 variant types, different from HNRNPH2 ones, span the entirety of hnRNPH1 (Gillentine et al, 2021). The main function of hnRNPH1/H2 is to control microexon inclusion and inhibition of cryptic polyadenylation sites during neurogenesis, safeguarding the integrity of the transcriptome.…”
Section: Downregulated Rna-binding Proteins For Alternative Splicing and Ribosome Biogenesis In Rubinstein-taybi Syndrome Ineuronsmentioning
confidence: 99%
“…RNASeq of iNeurons from individuals with Rubinstein–Taybi syndrome (RSTS, MIM# 180849, and #613684), an intellectual disability (ID) disorder caused by monoallelic pathogenic variants in the genes encoding CBP/p300 lysine acetyltransferases (Hennekam, 2006 ), revealed that RSTS-univocal downregulated genes (DRGs) encoding a coherent network of RNA-binding proteins (RBPs) are implicated in RNA processing and ribosome complex biogenesis (Calzari et al, 2020 ). Variation or misregulation of several genes for heterogeneous nuclear ribonuclear proteins (hnRNP), a well-characterized family of RBPs implicated in RNA splicing and processing (Geuens et al, 2016 ), has been linked to neurological and neurodevelopmental disorders supporting a variably shared molecular pathogenesis of disease subtypes that enhances the identification of new family-related NDD genes (Gillentine et al, 2021 ). Interestingly, like hnRNPs, lysine acetyltransferases have been identified as a gene family involved in RNA processing reaching the FDR significance from meta-analyses of >10.000 NDD exomes (Coe et al, 2019 ; Gillentine et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations